Attitudes towards implementation of the rights of children as formed by the media - Dudaitė, Jolita; Kairienė, Brigita (Special Education, 2017)
The article analyses the societal attitudes towards the rights of children and their implementation as formed by the media. The media has the possibility to reach a wide audience of readers. It serves as an important tool in encouraging the sensitivity of all society and those responsible for the protection of children’s rights policy. The aim of the research is to identify the implementation of children’s rights as affected by the media and to highlight those which are lacking. Attention is drawn to the implementation of the child’s rights in general, as well as those of the rights of children having special needs